2020
DOI: 10.1017/thg.2020.86
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Chronic Disease and Psychological Distress: An Australian Twin Study

Abstract: There is a commonly observed association between chronic disease and psychological distress, but many potential factors could confound this association. This study investigated the association using a powerful twin study design that can control for unmeasured confounders that are shared between twins, including genetic and environmental factors. We used twin-paired cross-sectional data from the Adult Health and Lifestyle Questionnaire collected by Twins Research Australia from 2014 to 2017. Linear regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Students with the history of chronic health conditions were more likely to experience psychological distress compared to those who did not. This is in line with a research conducted among Ugandan adolescents living with HIV [ 53 ] and supported by other studies that examined the relationship between psychological distress and chronic health conditions [ 10 , 54 ]. This could (among other factors) be attributed to adverse social circumstances and financial strain, reduced ability to cope with routine daily activities, and aggravated physical consequences such as pain and discomfort [ 55 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Students with the history of chronic health conditions were more likely to experience psychological distress compared to those who did not. This is in line with a research conducted among Ugandan adolescents living with HIV [ 53 ] and supported by other studies that examined the relationship between psychological distress and chronic health conditions [ 10 , 54 ]. This could (among other factors) be attributed to adverse social circumstances and financial strain, reduced ability to cope with routine daily activities, and aggravated physical consequences such as pain and discomfort [ 55 ].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, this may be due to the fact that adolescents are curious and are more likely to engage in risky behaviors such as alcohol consumption and smoking. Also, coupled with easy accessibility and availability of these substances as well as weak regulatory policies and enforcements in Uganda, school-going adolescents are exposed to substance use in early age and may be psychologically distressed due to the negative consequences of substance use [10,11,[18][19][20][21]. Previous studies conducted in Tanzania [12], Ethiopia [20], Zambia [11], India [8], Norway [21] and Finland [49] have all shown similar results although a study in Canada reported that alcohol and cannabis use were not associated with psychological distress among adolescents [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that, numerous studies have highlighted moderate associations between chronic diseases and psychological distress, irrespective of COVID-19. Nevertheless, findings from a twin-paired cross-sectional study indicate that the strength of the association between chronic diseases and psychological distress may be lower than previously presumed ( 75 ).…”
Section: Discussionmentioning
confidence: 84%
“…The outcome of interest was common chronic diseases in China, with chronic disease defined as a disease that is long-lasting with persistent effects [ 29 , 30 ]. Diseases were selected and grouped according to six major groups of commonly reported diseases in China [ 29 ].…”
Section: Methodsmentioning
confidence: 99%